Analysis of Family Allowance in the Context of Changes in the Income Tax on Individuals - Gołębiowski, Bartosz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
In modern economies, taxes have ceased to serve only fiscal functions - they are also a tool for regulating social and economic policy. As an essential element of the tax system, tax preferences make it possible for taxes to perform these functions. Frequent amendments result in increasing complexity of the tax system and the emergence of phenomena not previously observed. This article is based on the belief that the introduction of tax preferences in the form of pro-family tax relief in conjunction with other preferences and changes in tax law are the source of various dilemmas for the people affected. The existence of such dilemmas leads one to wonder whether pro-family tax relief is fair in terms of social justice and the principle of equal taxation. It is proven that in a particular case, this tax relief leads to the creation of "an unprofitable work area" - that is, a situation where, after a household reaches a certain income level, the amount of money available to it actually decreases.